Grape pomace transformed by specific fungi has the potential as a promising substrate for vermicomposting - Mar´ıa Ines Troncozo; Mart´ın Eduardo Escaray; Mar´ıa Florencia Vianna; Mario C. N. Saparrat (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: It is known that the combination of bioprocesses can contribute to obtaining better results compared to those achieved by applying each process individually. Solid state fermentation of Vitis labrusca grape pomace was carried out using different saprotrophic fungi following a vermicomposting process.